Pengaruh Pembiayaan Mudharabah, Musyarakah, dan Murabahah Terhadap Profitabilitas Bank Umum Syariah Periode 2015-2019 - Nevi Laila Khasanah; Taufik Mukmin (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2020)
The purpose of this study was to determine whether Mudharabah, Musyarakah, and Murabahah financing affected the profitability of Islamic Commercial Banks in Indonesia for the 2015-2019 period. This type of research is quantitative research. Quantitative research is to explain the position of the variables studied as well as the relationship between one variable with another variable. The research method used in this study uses descriptive quantitative research methods using multiple linear regression test. The quantitative method in this study was to examine the influence of Mudharabah, Musyarakah, and Murabahah financing on the profitability of Islamic Commercial Banks in 2015-2019. Based on the analysis and discussion of data described in the previous chapter on the effect of mudharabah, musyarakah, and murabahah financing on profitability (ROA) of Islamic banks, it can be concluded that the variables of mudharabah financing, musyarakah financing and murobahah financing significantly influence profitability (ROA). This is evidenced by the results of the t test where the significance value of the variable mudharabah financing (0.023), musyarakah financing (0.037) and murobahah financing (0.008) are more than 0.05. The profit sharing system will facilitate customers and the financing system is quite consumptive so that it can contribute to profit levels, which causes profitability to rise.